Akt inhibition synergizes with polycomb repressive complex 2 inhibition in the treatment of multiple myeloma. Issue 12 (22nd October 2019) - Rizk, Mohamed; Rizq, Ola; Oshima, Motohiko; Nakajima‐Takagi, Yaeko; Koide, Shuhei; Saraya, Atsunori; Isshiki, Yusuke; Chiba, Tetsuhiro; Yamazaki, Satoshi; Ma, Anqi; Jin, Jian; Iwama, Atsushi; et al.
Abstract: Polycomb repressive complex 2 (PRC2) components, EZH2 and its homolog EZH1, and PI3K/Akt signaling pathway are focal points as therapeutic targets for multiple myeloma. However, the exact crosstalk between their downstream targets remains unclear. We herein elucidated some epigenetic interactions following Akt inhibition and demonstrated the efficacy of the combined inhibition of Akt and PRC2. We found that TAS‐117, a potent and selective Akt inhibitor, downregulated EZH2 expression at the mRNA and protein levels via interference with the Rb‐E2F pathway, while EZH1 was compensatively upregulated to maintain H3K27me3 modifications. Consistent with these results, the dual EZH2/EZH1 inhibitor, UNC1999, but not the selective EZH2 inhibitor, GSK126, synergistically enhanced TAS‐117‐induced cytotoxicity and provoked myeloma cell apoptosis. RNA‐seq analysis revealed the activation of the FOXO signaling pathway after TAS‐117 treatment. FOXO3/4 mRNA and their downstream targets were upregulated with the enhanced nuclear localization of FOXO3 protein after TAS‐117 treatment. ChIP assays confirmed the direct binding of FOXO3 to EZH1 promoter, which was enhanced by TAS‐117 treatment. Moreover, FOXO3 knockdown repressed EZH1 expression. Collectively, the present results reveal some molecular interactions between Akt signaling and epigenetic modulators, which emphasize the benefits of targeting PRC2 full activity and the Akt pathway as a therapeutic option for multiple myeloma. Abstract : In this manuscript, we elucidate some epigenetic interactions following Akt inhibition and demonstrate the efficacy of the combined inhibition of Akt and PRC2. We found that TAS‐117, a potent and selective Akt inhibitor, differently controls PRC2 components, EZH2 and EZH1, in multiple myeloma. While EZH2 was downregulated, through Rb‐E2F stabilization, EZH1 was compensatively upregulated, to maintain H3K27me3 modifications. ChIP assays confirmed the direct binding of FOXO3 to EZH1 promoter, which was enhanced by TAS‐117 treatment. Moreover, the combination of TAS‐117 and the dual EZH1/2 inhibitor, UNC1999, but not the selective EZH2 inhibitor, GSK126, has a synergistic cytotoxic effect against multiple myeloma cell lines.